1997
DOI: 10.1055/s-0038-1655963
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Factor V Leiden Mutation in Non-European Populations

Abstract: SummaryA difference in the prevalence of venous thromboembolism (TE) in major human groups has been described and an uneven distribution of FV Leiden mutation over the world has recently been reported.We investigated FV Leiden mutation in 584 apparently healthy sub#jects mostly from populations different from those previously investi#gated: 170 Europeans (Spanish, Italians), 101 sub-saharan Africans (Fon, Bariba, Berba, Dendi), 115 Asians (Indonesians, Chinese, Tharus), 57 Amerindians (Cayapa), 84 Afroamerican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 18 publications
6
41
0
1
Order By: Relevance
“…by guest www.bloodjournal.org From African American controls. [25][26][27] The frequency of heterozygosity for the HR2 haplotype among whites also was similar to other studies, [15][16][17] but HR2 heterozygosity was infrequent among African Americans. In a separate LITE study report, we observed a higher risk of VTE among African Americans compared to whites, 18 and given race differences in risk factors such as factor V Leiden, additional study of African American populations is needed.…”
Section: Descriptive Findingssupporting
confidence: 88%
“…by guest www.bloodjournal.org From African American controls. [25][26][27] The frequency of heterozygosity for the HR2 haplotype among whites also was similar to other studies, [15][16][17] but HR2 heterozygosity was infrequent among African Americans. In a separate LITE study report, we observed a higher risk of VTE among African Americans compared to whites, 18 and given race differences in risk factors such as factor V Leiden, additional study of African American populations is needed.…”
Section: Descriptive Findingssupporting
confidence: 88%
“…For this reason, determining the prevalence of the FVL mutation in different populations has become an important means of taking decisions about which subjects at risk for thrombosis should be stratified for the FVL mutation. The data of this study should be helpful in formulating decisions about screening for FVL in patients of different populations, including the Brazilian population, since the results strengthen the observation that FVL is not prevalent among non-Caucasians (Rees et al, 1995;Arruda et al, 1996;Dählback, 1997;Pepe et al, 1997).…”
Section: Resultssupporting
confidence: 66%
“…It is well known that the allele frequencies for the factor V G1691A or factor II G20210A variants differ among various ethnic groups [87][88][89][90][91] ; for example, the factor V G1691A and factor II G20210A polymorphisms are rarely observed in blacks and Asians. In children with first-episode stroke, the homozygous MTHFR C677T mutation has been shown to independently increase the risk of stroke.…”
Section: Kenet Et Al Thrombophilia and Childhood Stroke 1843mentioning
confidence: 99%